Asking territories: the constituency orientation of Italian and French members of the European Parliament. (10th May 2016) - Sozzi, Fabio
Abstract : In this article, we explore how electoral systems influence attitudes and behavior of elected representatives. Focusing on constituency representation, we consider how variation in electoral systems may shape forms of political representation. An analysis of written parliamentary questions (PQs) is an important instrument to look at the role of parliamentarians even where, as in the European Parliament, political parties enforce discipline in roll-call voting. This kind of investigation offers the opportunity to partially resolve empirical and theoretical problems related to other methods of research. Unlike voting and speeches, PQs face fewer constrains from party leaders. This article analyses the constituency focus of members of European Parliament from France and Italy. These countries differ with regard to two main dimensions of electoral systems: ballot structure and district magnitude. The study is conducted through a content analysis of 5343 written PQs during the sixth term (2004–09). The results suggest that, despite the lack of strong electoral connection, electoral institutions shape the legislative behavior of the Italian and French parliamentarians providing incentives to cultivate personal reputation and constituency-orientation.